Funun Al-Badi’ Fi Suroh Al-Fathi: Dirasah Washfiyyah Tahliliyyah Balaghiyah - Abdul Muntaqim Al Anshory (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The Holy Quran was filled with the miracle of God, one of isBadi’. Badi’ is the sciences of rhetoric, which is the science of Arabic language, which examines the rules of the Arabic language method used in writing and conversation. Badi’ is looking at the meaning or the word in terms of decorating and refining it. Mahmoud Sheikhan said that he knew of the object of improving the speech that is appropriate and clear. The researcher looked for the science of Badi’ in Surrah Al-Fath because this surrah is Madaniyah surrah, The Victory surrah for believers on infidels. And its has characteristics by the other in terms of wonderful methods that indicate the eloquence of the Quran. The methodology of this research is qualitative descriptive approach. The result of the research is: 1. The verses that include the numerals: verses 2, 4, 5, 6, 7, 8, 9, 10, 11, 14, 15, 16, 17, 27, and 29; Verses containing the interview: verses 24 and 25. 2. The verses that include verbal enhancements in Surat Al-Fath are as follows: The verses that include the Courage: Verse 4-5, 11-13, 16-17, 19-20, 21-22, 25-26 and The verses that include the budget: Verse 6-11, 13-15, 18-19, 24-25, 27-29. Keyword: Badi’, Al-Fathi surrah.